Dengue virus: structura, serotypes and molecular epidimilogy - Laredo Tiscareño, Stephanie Viridiana (Universidad Autónoma de Tamaulipas, 2012)
Dengue fever is one of the most important viral diseases in the world. Dengue virus is transmitted to humans by Aedes aegypti mosquitoes. This virus is the causative agent of dengue fever and severe forms: dengue hemorrhagic fever and Dengue shock syndrome. There are four dengue virus serotypes. The virus spreads in two transmission cycles and considering the source of these infections, is classifi ed as urban and sylvatic. During viral infection and replication, eight proteins are involved in the generation and release of new viruses mature and infectious. In Mexico the first outbreaks of dengue virus appeared in 1941, getting re-emerge in 1978. Recently circulation of all four serotypes of dengue virus in Mexico has been confirmed. Each serotype has different grades of genetic diversity that raise several genotypes. These viral genotypes, contain several alterations in the order of the nucleotidic sequences. The study of the distribution of these genomic variants adds another level of complexity to the study of dengue infection in humans. The article illustrates the importance of Epidemiological of dengue disease and the genotypes that make up the dengue virus serotypes.